Brassica meal‐derived allyl‐isothiocyanate postharvest application: influence on strawberry nutraceutical and biochemical parameters. (19th March 2019) - Ugolini, Luisa; Pagnotta, Eleonora; Matteo, Roberto; Malaguti, Lorena; Di Francesco, Alessandra; Lazzeri, Luca
Abstract: BACKGROUND: The antimicrobial activity of allyl‐isothiocyanate (AITC) on plant pathogens is well known and has already been demonstrated in the strawberry with respect to Botritis cinerea fungal infection using postharvest biofumigation. In the present study, vapours of 0.08 mg L −1 of Brassica meal‐derived AITC were applied to strawberry to assess its effect on fruit nutraceutical and biochemical parameters after 2 days of storage at 20 °C and 90% relative humidity. RESULTS: Allyl‐isothiocyanate showed no detrimental effect on final strawberry quality, anti‐oxidant properties or ascorbic acid content. By contrast, an increased amount of asparagine and a higher ascorbate and glutathione redox potential were registered in the fruit soon after treatment. A reversible glutathione depletion action of AITC was also observed. Finally, total AITC residues in treated strawberry were quantified and a relatively high amount of AITC‐adducts was found in fruit tissues. CONCLUSION: The findings of the present study not only confirm the high potentiality of biofumigation with respect to extending the shelf‐life of fruit, but also provide some insight regarding the mechanisms of action of AITC at the cellular level as a possible elicitor of fruit protective responses. Nevertheless, the nature of the AITC‐adducts formed in fruit tissues needs further attention to enable a health and safety assessment of the final fruit. © 2019 Society of Chemical Industry